Cover Picture: Highly Hydrogenated Graphene through Microwave Exfoliation of Graphite Oxide in Hydrogen Plasma: Towards Electrochemical Applications (Chem. Eur. J. 46/2013). Issue 46 (30th October 2013) - Eng, Alex Yong Sheng; Sofer, Zdenek; Šimek, Petr; Kosina, Jiri; Pumera, Martin
<x xml:space="preserve">Abstract</x> Highly hydrogenated graphene is generated from graphite oxides by using a one‐step microwave‐irradiation process in hydrogen plasma. The procedure concurrently deoxygenates and hydrogenates the carbon backbone, as described in the Full Paper by M. Pumera et al. on page 15583 ff. The cover image shows the glow of hydrogen plasma during the microwave treatment.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>